2020
DOI: 10.1111/mec.15432
|View full text |Cite
|
Sign up to set email alerts
|

Gene regulation underpinning increased thermal tolerance in a laboratory‐evolved coral photosymbiont

Abstract: Small increases in ocean temperature can disrupt the obligate symbiosis between corals and dinoflagellate microalgae, resulting in coral bleaching. Little is known about the genes that drive the physiological and bleaching response of algal symbionts to elevated temperature. Moreover, many studies to‐date have compared highly divergent strains, making it challenging to accredit specific genes to contrasting traits. Here, we compare transcriptional responses at ambient (27°C) and bleaching‐relevant (31°C) tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 143 publications
(195 reference statements)
0
8
0
Order By: Relevance
“…This suggests that neither a coupled nor an uncoupled phenotype provides an advantage in terms of defining the capacity of a given species to adapt to global warming. However, we cannot exclude the possibility that other responses have been developed in long‐term heat‐stressed cells (Chakravarti et al ., 2020). Ecologically, this lack of adaptive capabilities in Symbiodiniaceae confirms the susceptibility of coral reefs to ocean warming.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that neither a coupled nor an uncoupled phenotype provides an advantage in terms of defining the capacity of a given species to adapt to global warming. However, we cannot exclude the possibility that other responses have been developed in long‐term heat‐stressed cells (Chakravarti et al ., 2020). Ecologically, this lack of adaptive capabilities in Symbiodiniaceae confirms the susceptibility of coral reefs to ocean warming.…”
Section: Discussionmentioning
confidence: 99%
“…However, no heat shock proteins were identified at significant levels in this study. Few coral bleaching studies have reported the presence of the chaperone proteins detected in the current study (Bellantuono et al, 2012;Maor-Landaw et al, 2014;Chakravarti et al, 2020).…”
Section: Protein Turnovermentioning
confidence: 54%
“…Interestingly, we also observed an upregulation of certain genes involved in ribosome function and protein digestion and absorption solely under heat stress conditions, suggesting their role in preventing the accumulation of damaged proteins. 65,66 However, the presence of herbicides impeded the regulatory capacity of these partially up-regulated genes, potentially hindering coral acclimatization to heat stress conditions. Moreover, co-stress on the 21st day was found to inhibit important pathways involved in phagosome and lysosome functions compared with heat stress alone (Figure 4a), implying impaired cellular functions in coral host cells.…”
Section: Presence Of Herbicide Prometryn Alteringmentioning
confidence: 99%